More than just finished: Unveiling the meaning of fukugodōshi ～owaru, ～ageru, and ～kiru in Japanese - Taqdir, Taqdir (Universitas Dian Nuswantoro, 2024)
This study explores the semantic distinctions of three Japanese fukugodōshi verbs: owaru, ageru, and kiru, which indicate varying degrees of action completion. Owaru signifies the general completion of an action without focusing on the result or perfection, while ageru emphasizes not only the completion but also the production of something valuable. Kiru, on the other hand, highlights the complete and thorough execution of an action without any remainder. This research aims to analyze how these verbs are used in formal contexts, specifically in Japanese media such as newspapers. Using a descriptive qualitative approach, articles from Asahi Shimbun and Mainichi Shimbun were selected to observe the use of these fukugodōshi verbs. Semantic analysis was conducted to explore the nuances conveyed by each verb in various contexts, providing deeper insights into how they reflect different levels of action completion. The findings of this study offer a clearer understanding of fukugodōshi usage in formal communication and contribute to Japanese language pedagogy, especially for learners to differentiate the appropriate usage of these verbs in specific contexts.